Prescription opioid use among individuals with serious mental illness. (September 2018) - Spivak, Stanislav; Cullen, Bernadette; Eaton, William; Nugent, Katie; Spivak, Amethyst; Fenton, Ashley; Rodriguez, Katrina; Mojtabai, Ramin
Highlights: Opioid use in those with serious mental disorders is nearly double the general population. Being on an opioid was associated with indicators of high risk use in those with serious mental illness, including history of heroin use and concurrent sedative-hypnotic use. Concurrent use of opioids with sedative-hypnotics was associated with suicidal ideation. Abstract: Prevalence and correlates of prescription opioid use were explored in individuals with serious mental illness (SMI) by examining a sample of adults from two inner city community psychiatry clinics. Of 271 participants, 12.9% ( n  = 35) were on a prescribed opioid. Being on an opioid was significantly associated with history of heroin use and active prescription sedative-hypnotic use, including benzodiazepine use. Concurrent use of opioids with sedative-hypnotics was significantly associated with suicidal ideation. The results highlight risks of prescription opioid use in those with SMI, particularly in combination with prescription sedative-hypnotics.